Does a screening trial for spinal cord stimulation in patients with chronic pain of neuropathic origin have clinical utility and cost-effectiveness (TRIAL-STIM)? A randomised controlled trial. Issue 12 (December 2020) - Eldabe, Sam; Duarte, Rui V.; Gulve, Ashish; Thomson, Simon; Baranidharan, Ganesan; Houten, Rachel; Jowett, Susan; Sandhu, Harbinder; Chadwick, Raymond; Brookes, Morag; Kansal, Anu; Earle, Jenny; et al.
Abstract : Abstract: Spinal cord stimulation (SCS) is an established treatment of chronic neuropathic pain. Although a temporary SCS screening trial is widely used to determine whether a patient should receive permanent SCS implant, its evidence base is limited. We aimed to establish the clinical utility, diagnostic accuracy, and cost-effectiveness of an SCS screening trial. A multicentre single-blind, parallel two-group randomised controlled superiority trial was undertaken at 3 centres in the United Kingdom. Patients were randomised 1:1 to either SCS screening trial strategy (TG) or no trial screening strategy (NTG). Treatment was open label, but outcome assessors were masked. The primary outcome measure was numerical rating scale (NRS) pain at 6-month follow-up. Between June 2017 and September 2018, 105 participants were enrolled and randomised (TG = 54, NTG = 51). Mean numerical rating scale pain decreased from 7.47 at baseline (before SCS implantation) to 4.28 at 6 months in TG and from 7.54 to 4.49 in NTG (mean group difference: 0.2, 95% confidence interval [CI]: −1.2 to 0.9, P = 0.89). We found no difference between TG and NTG in the proportion of pain responders or other secondary outcomes. Spinal cord stimulation screening trial had a sensitivity of 100% (95% CI: 78-100) and specificity of 8% (95% CI: 1-25). The mean incremental cost-effectiveness ratio of TG vs NTG was £78, 895 per additional quality-adjusted life-year gained. In conclusion, although the SCS screening trial may have some diagnostic utility, there was no evidence that an SCS screening TG provides superior patient outcomes or is cost-effective compared to a no trial screening approach. Abstract : Supplemental Digital Content is Available in the Text.The TRIAL-STIM randomised controlled trial found no evidence that a spinal cord stimulation screening trial strategy provides superior patient outcomes compared to a no trial screening approach.